2019
DOI: 10.1039/c9ee01726g
|View full text |Cite
|
Sign up to set email alerts
|

Cd-Free Cu2ZnSnS4solar cell with an efficiency greater than 10% enabled by Al2O3passivation layers

Abstract: Cd-Free CZTS solar cell with above 10% efficiency was achieved by an Al2O3 passivation layer prepared by ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 54 publications
2
125
1
1
Order By: Relevance
“…In recent time, earth-abundant and low-cost compound semiconductor materials like Cu 2 ZnSnS 4 (CZTS), Cu 2 ZnSnSe 4 (CZTSe), and Cu 2 ZnSn(S,Se) 4 (CZTSSe) have gained massive consideration as alternate materials instead of CIGS and CdTe as they have shown the efficiency of 10%, 11.95%, and 12.62%, respectively. [67][68][69] But, kesterite material consists of many elements. 70 The presence of many elements in the absorber layer increases the processing cost, and defects are also formed during the processing, which ultimately reduces the overall PCE of solar cells.…”
Section: Thin Lm Solar Cells (Tfscs)mentioning
confidence: 99%
“…In recent time, earth-abundant and low-cost compound semiconductor materials like Cu 2 ZnSnS 4 (CZTS), Cu 2 ZnSnSe 4 (CZTSe), and Cu 2 ZnSn(S,Se) 4 (CZTSSe) have gained massive consideration as alternate materials instead of CIGS and CdTe as they have shown the efficiency of 10%, 11.95%, and 12.62%, respectively. [67][68][69] But, kesterite material consists of many elements. 70 The presence of many elements in the absorber layer increases the processing cost, and defects are also formed during the processing, which ultimately reduces the overall PCE of solar cells.…”
Section: Thin Lm Solar Cells (Tfscs)mentioning
confidence: 99%
“…[ 4–6 ] However, the record efficiency of CZTSSe has stagnated at 12.6% for years. [ 5,7 ] Alkali incorporation has been considered as one of the most promising strategies for further enhancing the performance of kesterite solar cells. [ 8–11 ] The recent studies on lithium incorporation have demonstrated the most positive impact on optoelectronic properties of CZTSSe among all the alkali elements.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary tests of dielectric passivation on chalcogenides front surface have been studied [7,8,36]. However, no significant improvements in the CIGS device performance were observed [7,8] suggesting that a fundamental understanding of the dielectric physical properties and the impact of those layers on the CIGS optoelectronic properties are still needed.…”
Section: Introductionmentioning
confidence: 99%